THE EFFECT OF LIQUIDITY, SOLVENCY AND ACTIVITY ON PROFITABILITY WITH SALES GROWTH AS A MODERATING VARIABLE IN PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Septina Eka Nia Banurea; Solikah Nurwati; Agustina Muliyani (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective –  This study aims to analyze empirically the effect of liquidity, solvency, and activity on profitability with sales growth as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange. Design/Methodology/Approach –  This research uses Quantitative research. Sampling was carried out by purposive sampling, and obtained a sample of 20 sample companies. The data analysis method used is SmartPLS software. Findings – The results of this research analysis show that liquidity has no significant effect on profitability; solvency and activity have a significant effect on profitability; sales growth are not able to moderate the effect of liquidity, solvency, and activity on profitability. Conclusion and Implications – The liquidity has no significant effect on profitability; solvency and activity have an influence and are significant to profitability; sales growth is not able to moderate the influence of liquidity, solvency and activity on profitability. The company needs to innovate and evaluate strategies to increase the contribution of sales growth to the company. Investors and potential investors are more selective in choosing companies to invest in by paying attention to the company's financial condition.